FAKTOR - FAKTOR YANG MEMENGARUHI KINERJA PELAKSANA PROGRAM PENCEGAHAN DAN PENANGGULANGAN PENYAKIT DBD PUSKESMAS DI KABUPATEN ASAHAN TAHUN 2017 - NILAWARNI . (JURNAL ILMIAH SIMANTEK, 2019)
Currently the efforts to eradicate dengue have focused on eradicating Aedes Aegypti mosquitoes through the activities of eradicating mosquito nests (PSN) and the 3M movement (Covering, Draining and Burying). This study aims to find out what factors influence the performance of the program implementing prevention and control of DHF Puskesmas in Asahan District.This type of research is explanatory research research. The population in this study were all officers implementing the program of prevention and prevention of DHF Puskesmas in Asahan District, totaling 29 officers and at the same time became a sample in this study. The variables that were suspected to be influential were analyzed by using the chi-square statistical test and logistic regression at the 95% confidence level (p <0.05). The results showed that educational background, attitude and leadership had no effect on performance, while the ability, motivation and rewards affected the performance of the program implementing prevention and control of DHF at the Puskesmas in Asahan Regency. The most dominant variable is the reward variable with a value of B (3,759).Conclusion educational background, attitude and leadership have no effect on performance, while the ability, motivation and rewards affect the performance of the program implementing prevention and control of DHF Puskesmas in Asahan Regency. It is recommended to make training to improve performance, provide rewards for staff who have succeeded in reducing the number of DHF events in their working areas, make an allocation of incentives for DHF, Village and Community Health Centers to further enhance cooperation in monitoring the incidence of DHF.